Deferasirox-induced liver injury and Fanconi syndrome in a beta-thalassemia major male. Issue 7 (9th July 2020) - Fraser, Jacqueline; Brook, Rowena; He, Tony; Lewis, Diana
Abstract : A 33-year-old male presenting with subacute abdominal pain was found to have hyperbilirubinaemia, hypokalaemia and hyponatraemia. This was in the setting of transitioning between deferasirox iron chelator formulations, from dispersible tablets to film-coated tablets for ongoing treatment of chronic iron overload secondary to transfusion requirement for beta-thalassemia major. A liver biopsy demonstrated acute cholestasis with patchy confluent hepatocellular necrosis and mild to moderate microvesicular steatosis. Based on the histological, biochemical and clinical findings, the diagnosis of hepatotoxicity and Fanconi-like syndrome was made. The patient improved clinically and biochemically with cessation of the deferasirox film-coated tablets and supportive management. To our knowledge, this is the first case report of hepatotoxicity and Fanconi-like syndrome occurring due to deferasirox film-coated tablets with previous tolerance of dispersible deferasirox tablets. It is important to raise clinical awareness of this potentially severe complication.